Airborne Imaging Microwave Radiometer (AIMR) [NCAR/EOL/RSF] - UCAR/NCAR - Earth Observing Laboratory (Arctic Data Center)
This data set includes Airborne Imaging Microwave Radiometer (AIMR) measurements obtained from the NSF/NCAR C-130 aircraft (Tail Number: N130AR) during the Beaufort Arctic Storms Experiment (BASE) in 1994.